Genre recognition in the play of Lekhnath Paudyal’s poems - Adhikari, Anil (Adhyayan Journal, 2026)
Genre appropriation in Lekhnath Paudyal’s poetic dramas is the focus of this article’s analysis, and it constitutes the research problem. This article analyzes genre appropriation in the dramas ‘Shri Krishna-Leela’, ‘Teacher and Monk’, and ‘Narad and Science’. The analysis draws from library materials and a thorough reading of Lekhnath Paudyal’s poems. Genre fragmentation is studied in this article via meta-analysis, presented as a literary centered construction theory. Poetic drama is distinguished from other literary genres by its use of visual devices, dialogue schemes, conflict devices, and acting as its defining characteristics for genre identification. As the basis for genre identification in poetic drama, visual design, dialogue design, conflict design, and acting have been taken as the distinctive characteristic elements that distinguish drama from other literary genres. While poetry is a lyrical genre that freely explores life, drama’s genre identification is characterized by its integrated dramatic elements. In Poudyal’s poetry, visual design is crucial for content creation and establishing thematic poetic beauty. Moreover, the article concludes that the inclusion of dialogue and conflict in poetry has sacrificed its beauty for a dramatic narrative. It argues that through suitable acting direction and staging, the form has shifted into drama.